Diferença na contratilidade de ventrículos direito e esquerdo de ratos com e sem insuficiência cardíaca após o infarto do miocárdio - Fernandes, Aurélia Araújo (2006)
Coronary artery ligation is an experimental method used to induce myocardial infarction. The aim of this study was to analyze right and left ventricular performance in infarcted rats showing identical scar area. Infarcted rats with heart failure (INF-IC) were compared with asymptomatic rats (INF) and a control operated group (Sham). Eight weeks after surgery the scar area was similar between groups (INF= 26,5 ± 1,1 e INF-IC= 25 ± 0,9%). The left end diastolic pressure increased in the INF-IC group (16 ± 2,5 mmHg; p<0,05) but remained normal in the INF group (7,7 ± 0,7 mmHg) compared to Sham (5,2 ± 0,5 mmHg). Arterial and ventricular systolic pressures were similar in all groups. The increased right ventricular weight to body weight rate and the lung weight to body weight ratio differentiated rats with heart failure (INF-IC) from asymptomatic rats after infarction (INF) presenting same scar area. Isometric contractions from right ventricle strips (RV) and left ventricle papillary muscle were studied using a rate of stimulation of 0,5 Hz in Krebs solution at 30º C. Isometric force (normalized to muscle or strip weight, mg/g) in steady state condition was measured in the presence of [Ca+2]e (0,62; to 3,75 mM) and Isoproterenol (5x10-9 to 5x10-5 M) and during post rest potentiation. The positive inotropic response to calcium, Isoproterenol and post rest potentiation in the RV were preserved in the INF group but reduced in the INF-IC group (Ca2+ 3,75 mM: Sham= 163 ± 18 mg/g; INF= 148 ± 19 mg/g; INF-IC= 68 ± 11 mg/g; p<0,05); (Isoproterenol 5.10-5 M: Sham= 151 ± 15 mg/g, INF= 134 ± 17 mg/g, INF-IC= 52 ± 7 mg/g; p<0,05). The left ventricle papillary muscle contractile activity was reduced in both INF and INF-IC groups. These results demonstrate that myocardial infarction with same scar area might lead to different conditions, with and without heart failure. The left ventricle contractility was reduced in both groups. However, in the right ventricle contractility was reduced only in animals presenting heart failure. Results suggest the existence different remodeling mechanisms in the right ventricle after infarction in rats with same scar size depending on the presence or absence of heart failure.